2017
DOI: 10.1021/acssuschemeng.7b00240
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Formaldehyde: Content and Heat Generation in the Wood of Three Tree Species

Abstract: Global trends in allowable formaldehyde (CH2O) emissions from nonstructural wood-based composites require a renewed consideration of biogenic CH2O from wood. Increment cores from living Virginia pine (Pinus virginiana), yellow-poplar (Liriodendron tulipifera), and radiata pine (P. radiata) trees were used to measure CH2O and CH2O generation due to heating (200 °C, 10 min). Significant variations within and between trees of the same species were observed. Tissue types (juvenile/mature, heartwood/sapwood) someti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 18 publications
4
24
1
Order By: Relevance
“…Additionally, the emission rates were higher from the wood with higher MC. This is in line with earlier studies, where it has been noticed that higher MC promotes formaldehyde emissions from wood 51‐54 . Moreover, it has been shown by experimental and theoretical studies that emission rate of formaldehyde is positively related to both temperature and humidity 55 .…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the emission rates were higher from the wood with higher MC. This is in line with earlier studies, where it has been noticed that higher MC promotes formaldehyde emissions from wood 51‐54 . Moreover, it has been shown by experimental and theoretical studies that emission rate of formaldehyde is positively related to both temperature and humidity 55 .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, heating with high moisture levels produced more formaldehyde than from dry specimens. Radiata pine generated the highest levels of formaldehyde when heated, far exceeding the other species studied (Tasooji et al 2017). In another study, it was shown that formaldehyde emissions from pine wood chips before processing (ie cutting) were 25% lower than the emission from wood particles after processing, which was 4.6% of the emission permitted for E1-class products (Boruszewski et al 2011).…”
Section: Presence Of Oxidizing Agentsmentioning
confidence: 94%
“…Older trees contain more extractives than younger ones; especially, the extractives content of heartwood is higher in older trees than in younger ones [23,[42][43][44]. Experiments of Miranda et al [45], Morais and Pereira [46], and Tasooji et al [47] showed that heartwood, in general, contains significantly more extractives than the surrounding sapwood. Other parts like knots (the part of the branches inside the stem) or the bark contain even more and different accessory compounds [48][49][50].…”
Section: Content and Classificationmentioning
confidence: 99%